2020
DOI: 10.1017/s0007485319000877
|View full text |Cite
|
Sign up to set email alerts
|

The double-mutation(M918I + L1014F)kdrallele is fixed inCimex hemipterus populations in Guangxi, China

Abstract: AbstractFour putative knockdown resistance (kdr) mutations have been documented in the voltage-gated sodium channel (VGSC) gene of Cimex hemipterus from several countries. However, no information regarding kdr mutations in any Chinese tropical bed bug population is available to date. In this study, a double-mutation(M918I + L1014F)kdr allele was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…With the help of the SYBR green RT-PCR assay, the major kdr mutations were identi ed in all of the tropical bed bug samples. This nding, the same as the results of the previous studies [9,25,58,59], con rms the presence of high levels of pyrethroid resistance among our studied populations. This is a fact that makes the reconsideration of control programs, necessary and can be used as baseline information for proper management of resistance in other areas.…”
Section: Discussionsupporting
confidence: 92%
“…With the help of the SYBR green RT-PCR assay, the major kdr mutations were identi ed in all of the tropical bed bug samples. This nding, the same as the results of the previous studies [9,25,58,59], con rms the presence of high levels of pyrethroid resistance among our studied populations. This is a fact that makes the reconsideration of control programs, necessary and can be used as baseline information for proper management of resistance in other areas.…”
Section: Discussionsupporting
confidence: 92%
“…With the help of the SYBR Green and TaqMan real-time PCR assays, the major kdr/super-kdr mutations were identified in all of the tropical bed bug samples. The role of L1014F mutation in kdr- type resistance, reduction of target site sensitivity to pyrethroids, and M918I mutation with super-kdr resistance in C. hemipterus and several other insects have been affirmed in numerous earlier studies [ 9 – 13 , 15 , 16 , 21 , 25 , 59 62 ]. From the result of this study and those of previous investigations, it can be concluded that the populations of tropical bed bug in the studied areas could have a high level of resistance to pyrethroids.…”
Section: Discussionmentioning
confidence: 89%
“…For the reason that there is not a huge selection pressure to justify the emergence of such homogeneity in the kdr and super-kdr allele, the probability of implying the adaptive response to selective pressure hypothesis is lower, and it is more likely that the homogenous strains with super-kdr allele were introduced to Iran. Although the double mutation (M918I and L1014F) kdr allele was found in populations from Australia, India, Thailand, and China [ 19 , 25 , 59 ], the origin of this invasive pest in Iran is under question because the corresponding gDNA sequences of the target gene are not publicly available. Additional complimentary studies with microsatellite or mitochondrial markers, such as the study of Zhao et al [ 59 ], are suggested to clarify this hypothesis via investigating more samples from different populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COI haplotype found in infestations sampled in the Czech Republic and Slovakia was previously reported across many countries and appears to be the most common COI variant of C. hemipterus , at least in Asia. Similarly, the sodium channel variant, containing M918I and L1014F mutations, has been reported multiple times, from India and Australia (Dang et al ., 2015b), and from China (Zhao et al ., 2020), but not in Hawaii (Lewis et al ., 2020) or Sri Lanka (Punchihewa et al ., 2019). Although the country of origin cannot be pinpointed accurately at this time, the genetic uniformity of the Czech and Slovakian infestations may suggest a single introduction followed by spread.…”
Section: Discussionmentioning
confidence: 96%